Turizm : the Russian and East European tourist under capitalism and socialism - Gorsuch, Anne E.; Koenker, Diane, 1947- (Cornell University Press, 2006)
'Turizm' examines the history of tourism in Russia and eastern Europe from the tsarist period to the age of Soviet and east European mass tourism in the 1960s and 1970s.